IMPACT OF GLAUCOMA IN COGNITIVE DECLINE - Banerjee, Arijita; Khurana, Indu (Asian Journal of Pharmaceutical and Clinical Research, 2018)
ABSTRACT Purpose: To assess cognitive performance differences , if any,among primary open-angle glaucoma (POAG) patients, normal-tension glaucoma (NTG) patients, and healthy control (C) subjects. Methods: 60 age and sex matched subjects (20 POAG, 20 NTG, and 20 C subjects) were included in this study. Following routine ophthalmological examination the cognitive performance of all participants, detailed neurological examinations, including the mini-mental state examination (MMSE), were done. Results: The mean RNFL thicknesses were significantly different among the groups in the POAG, NTG, and C subjects, respectively;Â pÂ <0.001). MMSE scores were 24.1 Â± 2.4, 25.2Â Â± 3.8 and 28.9 Â± 0.9 in the POAG, NTG, and Controls groups, respectively. There were significant differences among the three groups (pÂ <0.001). Moreover, there were significant differences between the NTG and Controls groups (pÂ <0.001), and between the POAG and Controls groups (p<0.001). Conclusions: The overlapping pathogenesis in glaucoma and neurodegenerative disorders cause deterioration in cognitive performance. Decreased values of MMSE scoresÂ in POAG and NTG patients compared to the scores of healthy controls suggest a detailed neurological examination of glaucoma patients.Â Keywords: neurodegenerative disease, cognition, dementia, open angle glaucoma